Evolutionary origin of genomic structural variations in domestic yaks - Liu, Xinfeng; Liu, Wenyu; Lenstra, Johannes A.; Zheng, Zeyu; Wu, Xiaoyun; Yang, Jiao; Li, Bowen; Yang, Yongzhi; Qiu, Qiang; Liu, Hongyu; Li, Kexin; Liang, Chunnian; et al. (Nature communications, 2023)
Yak has been subject to natural selection, human domestication and interspecific introgression during its evolution. However, genetic variants favored by each of these processes have not been distinguished previously. We constructed a graph-genome for 47 genomes of 7 cross-fertile bovine species. This allowed detection of 57,432 high-resolution structural variants (SVs) within and across the species, which were genotyped in 386 individuals. We distinguished the evolutionary origins of diverse SVs in domestic yaks by phylogenetic analyses. We further identified 334 genes overlapping with SVs in domestic yaks that bore potential signals of selection from wild yaks, plus an additional 686 genes introgressed from cattle. Nearly 90% of the domestic yaks were introgressed by cattle. Introgression of an SV spanning the KIT gene triggered the breeding of white domestic yaks. We validated a significant association of the selected stratified SVs with gene expression, which contributes to phenotypic variations. Our results highlight that SVs of different origins contribute to the phenotypic diversity of domestic yaks. Yaks have been subject to natural selection, human domestication and interspecific introgression during their evolution. Here, the authors have identified genomic structural variations and the linked genes involved in these processes in domestic yaks, to reveal new insight into genetic basis of phenotypic diversity.